PENGETAHUAN SIKAP DAN PERILAKU MASYARAKAT TERHADAP PENGELOLAAN SAMPAH DI KOTA MANADO - , Robinson Pianaung ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Waste management basically requires active role of the community, especially in minimizing piles of waste, sorting waste, and making waste more useful. Waste problem at Manado Municipality based on the result of Basic Health Research is unavailability of waste disposal in the house (35.8%) and outside of the house (67.7%). Objective: To identify association between knowledge, attitude and behavior of the community in managing waste at Manado Municipality